Application Array Antenna To Improve Physical Layer Security In Noma Network - Trương Ngọc Hà,; Nguyễn Văn Phúc,; Đặng Phước Hải Trang,; Trần Thị Quỳnh Như, (Journal of Technical Education Science, 2024)
In this study, we propose a NOMA communication model combined with linear array antennas for the purpose of enhancing physical layer security. We introduce a model of 4 nodes: transmitter node S, receiver node D1, receiver node D2, eavesdropping node E. In which node S is equipped with an antenna array that can perform beamforming, 2 nodes D1 and D2 are 2 nodes that receive data x1, x2 is transmitted from Node S, Node E is an eavesdropping nodev will try to receive signals from S sent to x1, x2. To evaluate the ability to improve physical layer security, the study was based on the physical layer security outage probability parameter. Through the study, it has been concluded that, if the antenna array is combined, it will improve the physical layer security problem in NOMA technology quite well, the article concludes that depending on the location of Node E, the security bile is good or bad.